Data on effect of fire and herbivory on survival and height increment of saplings of five common European tree species. - Amsten, Karin; Cromsigt, Joris P. G. M.; Kuijper, Dries P. J.; Loberg, Jenny M.; Niklasson, Mats (Swedish University of Agricultural Sciences, 2021)
Fire and herbivory are fundamental top-down processes, structuring grass-tree ratios in ecosystems across a diversity of climates. Both are plant consumers that can strongly control the recruitment of woody seedlings or saplings to taller height classes. Without such ‘consumer control’, many grass-dominated ecosystems would convert into woodlands or forests. While extensively studied in savannas, few have explored the effects of these disturbance regimes on woody recruitment under temperate conditions.
We exposed saplings of the five most common European tree species to fire and herbivory in a full factorial experiment in a savanna-like wood-pasture on the Swedish west coast. After three years, we evaluated the effects of fire and herbivory on tree sapling survival and height increment. The tree species used, varying in traits and in expected response to fire and herbivory, were Scots pine Pinus sylvestris, Norway spruce Picea abies, European oak Quercus robur, Silver birch Betula pendula and Small-leaved lime Tilia cordata.
Fire and herbivory, and their combination, had a negative effect on both survival and height increment but with large differences among species. Sapling survival was reduced to a similar extent for all species except Q. robur, which was not affected by fire. Both processes, and the combination, reduced height increment of B. pendula, while only herbivory reduced the height increment of Q. robur. P. sylvestris, P. abies and T. cordata had a similar height increment in all treatments. Overall, the combined effect of fire and herbivory was similar to the effect of herbivory alone, indicating no additional effect of fire when herbivores were present.
Our experiment shows how fire and herbivory can cause a strong consumer control on the recruitment of European temperate trees on a wood-pasture, by reducing the recruitment of saplings to the next demographic stage. Responses to fire and herbivory differed from general predictions of species performance which highlights the need for further experiments addressing drivers of landscape openness and tree-grass interaction.
The data set consists of one file with data on tree saplings suvival and height increment, and one file with explanations to the variables.

Vetenskaplig studie om hur bete och brand påverkar överlevnad och tillväxt av trädplantor av fem vanliga Europeiska arter.
Innehåller en fil med överlevnad och höjdtillväxt på träden, samt en fil med förklaringar till variablerna.
Data över hur bete och brand påverkar överlevnad och tillväxt av trädplantor av fem vanliga Europeiska arter
Keywords: landscape ecology; landskapsekologi; Herbivory; Bete; Fire; Brand; Biological Sciences; Biologi; Ecology; Ekologi; Forest Science; Skogsvetenskap